Phosphorus release and realignment in anaerobic digestion of thermal hydrolysis pretreatment sludge - masking effects from high ammonium - Chen, Yun (2024)
Waste activated sludge (WAS) is a significant phosphorus (P) repository, and there is a growing interest in P recovery from WAS. Typically, the commercial technology for treating WAS involves thermal hydrolysis pretreatment (THP) coupled with anaerobic digestion (AD). However, there is ongoing debate regarding the transformation and distribution of P throughout this process. To address this, a long-term THP-AD process was operated in this study to comprehensively investigate P transformation and distribution. The results revealed that a substantial biodegradation of dissolved organic nitrogen (DON) raised the pH of the digestate to 8.3 during the AD process. This increased pH facilitated the dissolution of Al, leading to a reduction of 6.92 mg/L of NaOH-P. Simultaneously, sulfate reduction contributed to a decrease of 11.04 mg/L of Bipy-P in the solid. However, the reduction of Bipy-P and NaOH-P in the solid did not result in an improved P release to the supernatant. Conversely, a decrease of 23.60 mg/L P in the aqueous phase was observed after anaerobic digestion. The disappeared P was primarily precipitated with Mg and Ca, driven by the increased pH, and it contributed to the increase of HCl-P in the solid from 107.80 to 144.52 mg/L. These findings were further confirmed by results obtained from scanning electron microscopy (SEM), X-ray powder diffraction (XRD), and solid-state 31P nuclear magnetic resonance (NMR) spectroscopy. This study provides valuable insights into the mechanisms of P transformation during THP-AD process that is nearly opposite from conventional AD system.